Fully quantum-mechanical treatment of proton-hydrogen scattering - Abdurakhmanov, Ilkhom; Kadyrov, Alisher; Avazbaev, S.; Bray, Igor (2015)
© Published under licence by IOP Publishing Ltd. A fully quantum-mechanical convergent close-coupling approach to proton collisions with atomic hydrogen has been developed. Cross sections for target ionisation and electron capture by the projectile have been calculated in the energy range from 20 keV to 1 MeV. Calculated electron capture cross sections are in good agreement with the experiment, however for ionisation discrepancies between theory and experiment at intermediate energies still remain.